2023
DOI: 10.1039/d2tb02791g
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared rhodol dyes bearing salicylaldehyde moieties for ratiometric pH sensing in live cells during mitophagy and under hypoxia conditions

Abstract: We describe a simple but efficient approach to make fluorescent probes A and B based on rhodol dyes incorporated with salicyaldehyde moiety for monitoring pH changes in mitochondria under oxidative...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This consumption establishes a controlled baseline, optimal for scrutinizing NAD(P)H fluctuations in response to various treatments. 13,55 In our investigations, control larvae treated with probe C in PBS exhibited minimal fluorescence, indicating consumption of NAD(P)H (Figure 14). Upon exposure to different concentrations of NADH, we observed a dose-dependent rise in fluorescence, mirroring the increase in NAD(P)H levels (Figure 14).…”
Section: Visualizing Dynamic Cellular Nad(p)h Fluctuations Across Var...mentioning
confidence: 64%
See 2 more Smart Citations
“…This consumption establishes a controlled baseline, optimal for scrutinizing NAD(P)H fluctuations in response to various treatments. 13,55 In our investigations, control larvae treated with probe C in PBS exhibited minimal fluorescence, indicating consumption of NAD(P)H (Figure 14). Upon exposure to different concentrations of NADH, we observed a dose-dependent rise in fluorescence, mirroring the increase in NAD(P)H levels (Figure 14).…”
Section: Visualizing Dynamic Cellular Nad(p)h Fluctuations Across Var...mentioning
confidence: 64%
“…We employed freshly starved-hatched fruit fly larvae as a model system to assess the efficacy of probe C in monitoring NAD(P)H dynamics in vivo. 13,55 The selection of these larvae was due to their reduced NAD(P)H levels, a result of metabolic adjustments in response to lacking nutrients upon hatching. 13,55 In the absence of food, larval metabolism consumes NAD(P)H, a crucial coenzyme central to cellular reactions.…”
Section: Visualizing Dynamic Cellular Nad(p)h Fluctuations Across Var...mentioning
confidence: 99%
See 1 more Smart Citation
“…An MTT assay was utilized to verify the toxicity of the probes, as described previously. , A549 cells were subjected to either probe A or B , and the enzymatic reduction of the yellow MTT dye to a purple formazan product in the mitochondria was measured as an indicator of cell viability. The MTT assay shows that cell viability is above 80% under a concentration of 40 μM (Figures S18 and S19), indicating that the probes are of low toxicity to the cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…S15, ESI †). 26 The results indicated that both probes exhibited excellent biocompatibility, with cell viability maintained at 90% even at a high probe concentration of 50 mM (Fig. S15, ESI †).…”
Section: Probe Cytotoxicity and Photostabilitymentioning
confidence: 96%